Ipadayag ang kaanyag sa UP Mindanao an audio-visual presentation for UPCAT campaign - Bontanon, Kimberly Dawn V.
The University of the Philippines Mindanao (UP Mindanao) is a constituent unit of UP that is committed to provide quality and affordable education, with programs needed in the development of Mindanao and its neighboring regions. However, only a few people are aware of the existence of a UP Campus in Mindanao (Cabaral, 2010). Presently, there are few materials for the campaign such as brochures, posters and bookmarks but the existing materials were not enough for the said campaign. This study aims to produce an actual campaign that will help create a new strategy and a better promotional material that would disseminate information to the people in Mindanao and other regions through a promotional video made up of a series of photographs, moving visual images, and interviews. The target audience of this production study is not only the graduating high school students of public, private and science high schools in Mindanao, but also their advisers, guidance counselors, and principals, as well as the parents of the students. Herewith the promotional video will be the communication instrument that will help increase, as well as encourage the students to take the admission test, in order to have a large population in the university. The material will be used during the UPCAT campaign of the OUR and will be circulated to the different regions in Mindanao.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts